EFEKTIVITAS SWEDISH MASSAGE THERAPY (SMT) PADA IBU LANSIA SEBAGAI UPAYA PENATALAKSANAAN HIPERTENSI DI POSYANDU LANSIA - Intarti, Wiwit Desi; Puspitasari, Lina; Oktaviani, Anisa Sevi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Hypertension is a silent killer disease, because most did not show the presence of signs and symptoms. Hypertension are at risk of heart attack and stroke. Swedish Massage Therapy (SMT) is a method of massage of the whole body in a decrease in blood pressure in elderly mother. The purpose of this research is to know the effectiveness of Swedish Massage Therapy (SMT) on elderly hypertension treatment as an attempt at Posyandu elderly. Research methods used in the form of a quantitative study design true-experimental with pretest-posttest control group design with Randomize Controlled Trial (RCT). The number of the population of the elderly, mothers with 656 technique of sampling purposive sampling of 60 respondents consisted of 30 in the intervention group and 30 in the control group. Data analysis techniques using test man whitney with SPSS programme 20. Research results show that the data is not normal with the value berditribusi sig: 0.008 kolmogorov test at the 0.05 <-smirnov and sig: 0.004 test at 0.05 < shapiro-wilk. So the data analysis done with test statistics as mann-whitney test with a value of z: – 5.69 and p value: 0.001, Ho and Ha rejected accepted. There is a summary of the effectiveness of Swedish Massage Therapy (SMT) on elderly hypertension treatment as an attempt at Posyandu elderly. Keywords: SMT, Elderly, Hypertension